Impact on entrepreneurship towards economic performance in Malaysia / Ahmad Ghazali Ismail, Abdul Kadir Rosline and Mohammad Firdaus Mohamad - Ismail, Ahmad Ghazali; Rosline, Abdul Kadir; Mohamad, Mohammad Firdaus (Universiti Teknologi MARA, 2018)
Entrepreneurship has emerged as an important element in the organization of economies. The contribution of entrepreneurship towards economic growth has been discussed by a number of studies. Therefore, this study is to determine the relationship between entrepreneurship and economic growth in the context of Malaysia, by using self-employment to explain entrepreneurship while GDP is applied to explain economic growth. This study observed data from the year 1991 to 2016. This study used empirical tests of Johannsen Cointegration to achieve the objectives. The outcomes show that there is a long run cointegration among variables. Additionally, when applying Granger Causality test, the study found that there is unidirectional causality from economic growth towards entrepreneurship.